Comparative Anatomy of the Forearm and Hand of Wildcat (Leopardus geoffroyi), Ocelot (Leopardus pardalis) and Jaguar (Panthera onca) - Sánchez, H. L.; Rafasquino, M. E.; Portiansky, E. L. (Journal of Morphological Sciences, 2019)
Introduction The thoracic limbs of cats facilitate jumping and represent one of their main ways for pursuing and capturing prey. The main muscles and nerves involved in these activities are present in the region of the forearm and of the hand. The scant anatomical reference availabe on South American cats species justifies the present comparative study.Materials and Methods The forelimbs of wildcat, ocelot and jaguar wild felines were fixed. Images of the dissected limbs were captured using a digital camera. Measurements were made using a caliper.Results The long and short heads of the extensor carpi radialis muscle of the ocelot and of the jaguar showed a great development in comparison with those of the wildcat. The flexor digitorum profundus muscle in the three felines is formed by five heads. In the jaguar, the radial or deep head presented two sesamoid bones. The brachioradialis muscle of the jaguar and of the ocelot is inserted medially at the distal end of the radius and at the proximal row of the carpus by a thick and flattened tendon. The pronator teres muscle of the jaguar extended to the carpal region. In the wildcat and in the ocelot, this muscle was less developedConclusions The main variations observed between the forearms and the hands of these South American cats were found between the supinator and the pronator muscles, presenting a variation in the size of their bellies and tendons. Our study of the muscular characteristics represents a contribution to the homologies and differences of the forearm and hand muscles of each of these species of felines.
Keywords: South American felines; felines; forearm muscles; hand muscles; jaguar; ocelot; wildcat